2018
DOI: 10.1002/ente.201700957
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Decarboxylation of Corn Distillers Oil for Fuel‐Grade Hydrocarbons

Abstract: Catalytic hydrothermal conversion of non‐edible corn distillers oil (CDO), a low‐value by‐product of the ethanol industries, into high value fuel‐grade hydrocarbons was investigated in near‐supercritical water. The decarboxylation experiments were conducted using activated carbon in a 300 mL batch stirred tank reactor at reaction temperatures of 300–400 °C with pressure ranges from 2200–2500 psi (≈15–17 MPa), water/CDO (v/v) ratios of 2:1 to 5:1, and reaction times of 0.5 to 4 h at constant stirring speed (800… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…It was comparable to the highest yield of heptadecane. However, compared with temperatures of 300 °C and 330 °C, there is a decrease in CO2 19) . It is consistent with this study's findings that there is an increase and decrease in CO2 gas production.…”
Section: Fig 2: Conversion Of Palm Olein After 4 H At Different React...mentioning
confidence: 90%
See 3 more Smart Citations
“…It was comparable to the highest yield of heptadecane. However, compared with temperatures of 300 °C and 330 °C, there is a decrease in CO2 19) . It is consistent with this study's findings that there is an increase and decrease in CO2 gas production.…”
Section: Fig 2: Conversion Of Palm Olein After 4 H At Different React...mentioning
confidence: 90%
“…In an autoclave with a 500 mL volume, palm olein was deoxygenated hydrothermally at various temperatures of 330 -400 °C) with pressure range from 52-230 bar. Reactants are palm olein oil (30 grams), deionized water (120 grams), and activated carbon pellets (21 grams) were loaded for a typical reaction 19). After purging and filling with N2 gas under static conditions, the autoclave's temperature was adjusted to the reaction condition.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that deoxygenation of saturated and unsaturated fatty acids can be conducted at near supercritical water temperature with a selectivity over 90% towards HCO 2 products, but the molar yield of HCO 2 products obtained was only 6 %. Other than supercritical water, Hossain et al [189,199] and Edeh et al [186] exploited the diffusivity of subcritical water in the deoxygenation of fatty acid derivatives and corn oil into diesel-like hydrocarbons, both demonstrated excellent n-alkanes selectivity and liquid yield. In the same theme, both Vardon et al [198] and Hollak et al [200] employed hydrothermal aqueous phase reforming of glycerol for in-situ hydrogen production and the catalytic HCO 2 of triglycerides.…”
Section: Effect Of Hydrogen Donor Solvent/co-solventmentioning
confidence: 99%